Pierre Culot : 1938-2011 - Bony, Anne; Duguet, Emmanuelle; Fournier, Karl; Tyas, Matthew (Brussels : Mercatorfonds, 2023)
Monografie over keramiekkunstenaar en beeldhouwer Pierre Culot
kunstcatalogus
Keywords: Culot, Pierre